Терміни та номенклатурні одиниці в наукових текстах - Євтухов, Д. О. (ХНУРЕ, 2021)
This report is devoted to terms and nomenclature units in scientific texts. The report clarifies their role in scientific texts, the difference between these two concepts and why in general terms and nomenclature units are used
Keywords: українська державність; українознавство